A Content Analysis of Gender Bias in When English Rings A Bell Textbooks - Lisa Julianti; Ikhsanudin Ikhsanudin; Yohanes Gatot Sutapa Y (Universitas Tanjungpura, 2019)
This thesis reports on the gender bias contained in English e-textbook for junior high school students provided by the ministry of education. The study used a framework proposed by Porreca (1984) as guidance. The framework is distinctive because it examines the problem of gender representation contained in textbook. Based on the framework the study focused on gender visibility in text and illustration, gender firstness, occupational role, gender neutral nouns and gender specific nouns, masculine generic construction, and adjectives. The finding reveals that although there is an effort to avoid gender bias, females are still represented traditionally in some categories. When females are portrayed traditionally in the textbook, students develop a stereotype view towards female students.